Exposure of patients to ionising radiation during lung cancer diagnostic work-up. Issue 9 (25th April 2017) - Rintoul, Robert C; Atherton, Rachel; Tweed, Katharine; Yates, Stuart; Chilvers, Edwin R
Abstract : We examined the dose of radiation received during diagnosis of lung cancer as this may add to the risk of a second primary cancer. Patients undergoing surgery (n=40) or (chemo)radiotherapy (n=40) received comparable doses (28.6 and 25.8 mSv, respectively), significantly higher than that for supportive care (n=40; 15.1 mSv). The effective dose of radiation received was higher for early stage disease than for those with metastatic disease. The mean lifetime attributable risk of malignancy for those receiving treatment with curative intent in our cohort was 0.059%, and lung-specific risk 0.019%.